(untitled) (Nexo Revista Científica, 2022)
The article is devoted to the assessment of the impact of air transport on the development of the tourism industry. It has been established that air carriers around the world provide a significant share of international tourist trips and are dependent on fluctuations in tourist demand. It has been determined that the understanding of the need to study the degree of interdependence between the tourism and aviation business transforms traditional approaches to the study of tourism and aviation transport. The analyzed functional links between travel companies and airlines allowed asserting the formation of a specialized system, the logistics principles of which will enable people to maximize their mobility potential in the modern globalized world. It has been proved that the development of air transport becomes a decisive factor in the development of tourism, its driving force. For effective joint activities of airlines with tourist enterprises, it is necessary to develop such ways of their interaction that will allow them to function in a coordinated manner within the framework of a single chain of providing tourist services.